Evaluation of two cell culture media in culturing rat full term amniotic fluid cells - Ferdaos, Nurfarhana; Karrupiah, Thilakavathy; Rosli, Rozita; Yazid, Mohd Nazri; Nordin, Norshariza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Introduction: Amniotic fluid (AF) consists of heterogenous population of cells with high diagnostic and therapeutic values. The study of rat amniotic fluid cells is very limited, despite the extensive use of this animal model in biomedical research. Primary culture of rat AF cells, especially from full term pregnancies has not been well established. Here we attempt to determine the suitable medium in culturing rat AF cells that would enhance the cell viability, growth rate and heterogeneity. Methods: The cell viability, growth rate and heterogeneity of rat AF cells were compared upon culturing the primary cells in two different media; Amniomax or RPMI. Cell viability study was carried out using trypan blue staining, while the growth rate was monitored based on the time required to passage the cells (population doubling time in hour). The heterogeneity of cells was examined based on the morphology of the cells. Statistical analysis was performed using t-test. Results: Amniomax was observed to provide a better culture condition in culturing rat AF cells as the cells are more viable, grow faster and more heterogenous as compared to the cells grown in RPMI. Conclusion: Amniomax is a more suitable medium for high quality and viability of full term rat AF cell culture, as compared to RPMI. Thus, warranting propagation of more rat AF cells for biomedical research.